Scratch-resistant stone-plastic composite floor and preparation method thereof

By using a protective surface layer composed of silica powder and reinforcement additives on the stone-plastic composite floor, the problem of insufficient scratch resistance in the prior art is solved, and the good scratch resistance and toughness of the floor are achieved.

CN119955382APending Publication Date: 2025-05-09JIANGSU ZHONGXIN HOME NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510106796.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The existing protective coatings of stone-plastic composite floors have insufficient scratch resistance and are prone to scratches. Methods to improve scratch resistance will lead to increased brittleness of the coating and difficult to improve scratch resistance.

Method used

The protective surface layer consisting of silica micropowder, reinforcement additives and acrylate resin is used to form an organic-inorganic cross-linking network through the reinforcement additives and silica micropowder, which improves the hardness and toughness of the protective surface layer.

Benefits of technology

It achieves good scratch resistance of stone-plastic composite flooring, and the protective surface layer is not easily scratched, while maintaining moderate toughness to avoid the occurrence of brittle microcracks.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a scratch-resistant stone-plastic composite floor and a preparation method thereof, and belongs to the technical field of floors. The composite floor is composed of a co-extrusion stone-plastic base plate and a protective surface layer, wherein the protective surface layer comprises the following components: 14-18 wt% of silicon dioxide micro powder, 3.5-5.2 wt% of a strengthening auxiliary agent, 5.5-7 wt% of a reactive diluent, 0.15-0.2 wt% of a defoaming agent, 0.3-0.4 wt% of a leveling agent and the balance of acrylate resin; the strengthening aid is prepared by the following steps: substituting active amino groups of 1-chloropropanol and p-aminofluorobenzene to prepare an intermediate, reacting methacryloyl chloride with hydroxyl groups introduced into molecules of the intermediate to prepare a modifier, and finally further performing quaternization on iodopropyltrimethoxysilane and a tertiary amine structure in the modifier, and introducing a trimethoxysilane structure, so as to obtain the strengthening aid. And the reinforcing auxiliary agent and the silicon dioxide have a synergistic effect, so that deep scratches of a scratched object are prevented, the generation of tearing scratches is reduced, and excellent scratch resistance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flooring, and in particular relates to a scratch-resistant stone-plastic composite flooring and a preparation method thereof. Background Art

[0002] Stone plastic composite material is a new type of material made of stone powder and polyvinyl chloride resin as the main components, supplemented by a variety of additives, and extruded under high temperature and high pressure. Compared with traditional wood materials, stone plastic composite materials have excellent physical and chemical properties due to the combination of multiple advantages of stone plastic composite materials and polyvinyl chloride resin, mainly including: high dimensional stability, waterproof and corrosion resistance, green and environmentally friendly, renewable, free of pollutants, and recyclable, and are widely used in floor materials.

[0003] However, the color and texture of stone-plastic composite materials are difficult to meet people's diverse decorative needs. The colors are monotonous and lack personalized expression. Generally, stone-plastic composite floors are co-extruded with a decorative layer and an anti-wear layer on the surface of the stone-plastic substrate, and a functional protective coating is compounded on the surface; these protective coatings mostly use solvent-free photocurable resins as film-forming materials, with high production efficiency and no pollution during the production process, which matches the environmental protection advantages of stone-plastic floors; however, the existing photocurable resins have insufficient scratch resistance and are easily scratched during the installation and use of the floor, affecting the aesthetics of the floor; in the prior art, in order to improve the scratch resistance of the protective coating, a resin with a high degree of cross-linking is generally used as a film-forming material, or a large amount of fillers are added to prevent the scratching object from penetrating into the scratches by increasing the hardness of the coating. However, with the increase in hardness, the brittleness of the coating increases, and microcracks are easily generated under the impact of scratching. In addition, the increase in hardness also leads to an increase in the resistance of the scratching object in the scratch, which is easy to form tearing scratches, and then the scratch resistance of the coating is difficult to improve. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a scratch-resistant stone-plastic composite floor and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A scratch-resistant stone-plastic composite floor consists of a co-extruded stone-plastic substrate and a protective surface layer, wherein the protective surface layer comprises 14-18wt% of silicon dioxide powder, 3.5-5.2wt% of a reinforcing auxiliary agent, 5.5-7wt% of an active diluent, 0.15-0.2wt% of a defoaming agent, 0.3-0.4wt% of a leveling agent, and the balance is acrylic resin.

[0006] The strengthening aid is prepared by the following method: Step A1: premix 1-chloropropanol and acetone, pass nitrogen protection, then add p-aminofluorobenzene, heat to 50-60°C and reflux, absorb the reflux tail gas with an alkaline drying tube, apply stirring at 120-150rpm to react for 5-7h, and after the reaction, remove acetone by rotary evaporation, wash the substrate with water, separate the liquid to remove the water phase, and dry in vacuo to obtain an intermediate; Furthermore, the feed ratio of p-aminofluorobenzene, 1-chloropropanol and acetone is 0.1 mol: 0.22-0.24 mol: 80-100 mL, and 1-chloropropanol is fully substituted with the active amino group of p-aminofluorobenzene to form a fluorine-containing tertiary amine compound.

[0007] Step A2: premix the intermediate, p-toluenesulfonic acid and tetrahydrofuran, introduce dry air protection, apply stirring at 30-40 rpm at room temperature, slowly add methacryloyl chloride to react for 1.2-1.6 hours, then raise the temperature to 40-50°C and continue to react for 2-3 hours. After the reaction is completed, remove tetrahydrofuran by rotary evaporation to obtain a modifier; Furthermore, the feed ratio of the intermediate, methacryloyl chloride, p-toluenesulfonic acid and tetrahydrofuran is 0.1 mol: 0.2 mol: 0.4-0.6 g: 50-70 mL, and the methacryloyl chloride reacts with the hydroxyl group introduced into the intermediate molecule to graft the methacrylate structure.

[0008] Step A3: premix the modifier, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane, pass dry air for protection, then add iodopropyltrimethoxysilane and mix well, heat to 70-80°C, stir at 60-90 rpm for reaction for 3-4 hours, filter after the reaction, and remove dioxane by rotary evaporation to obtain a strengthening agent; Furthermore, the feed ratio of the modifier, iodopropyltrimethoxysilane, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane is 0.1 mol: 0.1 mol: 0.1-0.15 g: 1.4-1.9 g: 150-200 mL, and the iodopropyltrimethoxysilane and the tertiary amine structure in the modifier are further quaternized to introduce the trimethoxysilane structure.

[0009] Preferably, the acrylate resin is selected from difunctional acrylates and maintains moderate toughness after curing.

[0010] Preferably, the acrylate resin is selected from bisphenol A epoxy acrylate, and the cured layer has high hardness and moderate brittleness, and is suitable for surface protection of floors.

[0011] Preferably, the active diluent is selected from glycidyl methacrylate, which has good dilution performance and good cross-linking properties with acrylate resin, thereby improving the scratch resistance of the cured layer.

[0012] Preferably, the silicon dioxide powder is selected from submicron powders and has moderate dispersibility.

[0013] Preferably, the defoaming agent and the leveling agent are both selected from organosilicon compounds.

[0014] A method for preparing a scratch-resistant stone-plastic composite floor comprises the following steps: Step S1: premixing acrylic resin, reinforcing agent, active diluent, defoaming agent and leveling agent, adding silica powder and mixing, and vacuum degassing to obtain protective slurry; Step S2: Apply the protective slurry to the surface of the co-extruded stone-plastic substrate, pre-bake and level it, and then send it into a UV curing furnace for UV radiation curing to form a protective surface layer. After cutting, a scratch-resistant stone-plastic composite floor is obtained.

[0015] Beneficial effects of the present invention: The invention endows the stone-plastic composite floor with good scratch resistance through a protective surface layer. The protective surface layer uses acrylic resin as a film-forming substrate and can be formed by a photocuring process. The process is simple, the production efficiency is high and there is no pollution. Compared with the existing photocuring coating, the invention effectively improves the scratch resistance of the protective surface layer through the synergistic effect of a reinforcing auxiliary agent and silica micropowder, while maintaining good toughness. The reinforcing auxiliary agent is fully substituted by the active amino group of 1-chloropropanol and p-aminofluorobenzene to form a fluorine-containing tertiary amine compound, i.e., an intermediate. Then, methacryloyl chloride reacts with the hydroxyl group introduced in the intermediate molecule to graft a methacrylate structure to obtain a modifier. Finally, iodopropyltrimethoxysilane and the tertiary amine structure in the modifier are further quaternized to introduce a trimethoxysilane structure to obtain a reinforcing auxiliary agent. In the process of forming the protective surface layer, the reinforcing auxiliary agent is The methoxysilane in the additive is coupled and compounded with the surface of the silica particles, and an acrylate structure is introduced into the silica surface. After curing, the silica and the matrix form an organic-inorganic cross-linked network, which effectively improves the hardness of the protective surface layer, thereby making the protective surface layer less susceptible to scratches. The strengthening additive introduces low surface energy fluorine elements into the silica surface, which are dispersed in the outer layer of the silica under the effect of segregation. On the one hand, the force between the macromolecular chains is weakened, so that the protective surface layer maintains moderate toughness, and is not prone to brittle microcracks under the action of external scratches, thereby maintaining the integrity of the protective surface layer structure. On the other hand, silica, as a hard medium, hinders the penetration of scratching objects and causes scratches to intensify. The fluorine structure of the outer layer acts as a lubricant, reduces the friction coefficient between the scratching objects and the silica, and reduces the generation of tearing scratches, thereby achieving excellent scratch resistance. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Example 1, preparation of scratch-resistant stone-plastic composite floor, the specific implementation process is as follows: (1) Preparation of strengthening additives Step A1: premix 1-chloropropanol and acetone, pass nitrogen protection, then add p-aminofluorobenzene, heat to 50°C and reflux, absorb the reflux tail gas with an alkaline drying tube, and stir at 120rpm for 7h, wherein the feed ratio of p-aminofluorobenzene, 1-chloropropanol and acetone is 0.1mol:0.22mol:80mL. After the reaction, remove acetone by rotary evaporation, wash the substrate with water, separate the liquid to remove the water phase, and dry in vacuo to obtain an intermediate.

[0018] Step A2: pre-mix the intermediate, p-toluenesulfonic acid and tetrahydrofuran, introduce dry air protection, apply stirring at 30 rpm at room temperature, slowly add methacryloyl chloride to react for 1.6 hours, then raise the temperature to 40°C and continue the reaction for 3 hours, wherein the feed ratio of the intermediate, methacryloyl chloride, p-toluenesulfonic acid and tetrahydrofuran is 0.1 mol: 0.2 mol: 0.4 g: 50 mL. After the reaction is completed, remove tetrahydrofuran by rotary evaporation to obtain a modifier.

[0019] Step A3: pre-mix the modifier, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane, pass dry air for protection, then add iodopropyltrimethoxysilane and mix well, heat to 70°C, and stir at 60rpm for 4h, wherein the feed ratio of the modifier, iodopropyltrimethoxysilane, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane is 0.1mol: 0.1mol: 0.1g: 1.4g: 150mL. After the reaction is completed, filter and remove dioxane by rotary evaporation to obtain a strengthening auxiliary agent.

[0020] (2) Preparation of scratch-resistant stone-plastic composite flooring Step S1: Take the raw materials according to weight percentage, 14wt% of silica powder, selected from submicron powder with an average particle size of 0.3μm; 3.5wt% of reinforcing agent, homemade in this embodiment; 7wt% of active diluent, selected from industrial-grade glycidyl methacrylate; 0.2wt% of defoamer, selected from commercially available THIX-278 type silicone defoamer; 0.3wt% of leveling agent, selected from commercially available TEGO Glide100 type silicone leveling agent; the balance is difunctional B-100 type bisphenol A epoxy acrylate; first, pre-mix the acrylate resin, reinforcing agent, active diluent, defoamer and leveling agent at 180rpm for 5min, then reduce the stirring rate to 30rpm, add silica powder and mix for 30min, and vacuum degassing for 10min to obtain a protective slurry.

[0021] Step S2: Take a three-layer co-extruded stone-plastic substrate containing a stone-plastic layer, a decorative layer and an anti-wear layer, apply a 0.3 mm thick protective slurry on the surface, pre-bake and level at 60°C for 10 minutes, and send it into a UV curing oven at 120W / m 2 The protective surface layer is formed by ultraviolet radiation curing, and the scratch-resistant stone-plastic composite floor is obtained after cutting.

[0022] Example 2, preparation of scratch-resistant stone-plastic composite floor, the specific implementation process is as follows: (1) Preparation of strengthening additives Step A1: premix 1-chloropropanol and acetone, pass nitrogen protection, then add p-aminofluorobenzene, heat to 60°C, reflux and absorb the reflux tail gas with an alkaline drying tube, apply 150rpm stirring to react for 5h, wherein the feed ratio of p-aminofluorobenzene, 1-chloropropanol and acetone is 0.1mol:0.24mol:100mL. After the reaction, remove acetone by rotary evaporation, wash the substrate with water, separate the liquid to remove the water phase, and vacuum dry to obtain an intermediate.

[0023] Step A2: pre-mix the intermediate, p-toluenesulfonic acid and tetrahydrofuran, introduce dry air protection, apply stirring at 40 rpm at room temperature, slowly add methacryloyl chloride to react for 1.2 hours, then raise the temperature to 50°C and continue the reaction for 2 hours, wherein the feed ratio of the intermediate, methacryloyl chloride, p-toluenesulfonic acid and tetrahydrofuran is 0.1 mol: 0.2 mol: 0.6 g: 70 mL. After the reaction is completed, remove tetrahydrofuran by rotary evaporation to obtain a modifier.

[0024] Step A3: pre-mix the modifier, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane, introduce dry air for protection, then add iodopropyltrimethoxysilane and mix well, raise the temperature to 80°C, and stir at 90rpm for 3h, wherein the feed ratio of the modifier, iodopropyltrimethoxysilane, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane is 0.1mol: 0.1mol: 0.15g: 1.9g: 200mL. After the reaction is completed, filter, and remove dioxane by rotary evaporation to obtain a strengthening auxiliary agent.

[0025] (2) Preparation of scratch-resistant stone-plastic composite flooring Step S1: Take the raw materials according to weight percentage, 18wt% of silica powder, selected from submicron powder with an average particle size of 0.3μm; 5.2wt% of reinforcing agent, homemade in this embodiment; 5.5wt% of active diluent, selected from industrial-grade glycidyl methacrylate; 0.15wt% of defoamer, selected from commercially available THIX-278 type silicone defoamer; 0.4wt% of leveling agent, selected from commercially available TEGO Glide100 type silicone leveling agent; the balance is difunctional B-100 type bisphenol A epoxy acrylate; first, pre-mix the acrylate resin, reinforcing agent, active diluent, defoamer and leveling agent at 180rpm for 5min, then reduce the stirring rate to 30rpm, add silica powder and mix for 30min, and vacuum degassing for 10min to obtain a protective slurry.

[0026] Step S2: Take a three-layer co-extruded stone-plastic substrate containing a stone-plastic layer, a decorative layer and an anti-wear layer, apply a 0.3 mm thick protective slurry on the surface, pre-bake and level at 60°C for 10 minutes, and send it into a UV curing oven at 120W / m 2 The protective surface layer is formed by ultraviolet radiation curing, and the scratch-resistant stone-plastic composite floor is obtained after cutting.

[0027] Example 3, preparation of scratch-resistant stone-plastic composite floor, the specific implementation process is as follows: (1) Preparation of strengthening additives Step A1: premix 1-chloropropanol and acetone, pass nitrogen protection, then add p-aminofluorobenzene, heat to 55°C, reflux and absorb the reflux tail gas with an alkaline drying tube, apply 150rpm stirring to react for 6h, wherein the feed ratio of p-aminofluorobenzene, 1-chloropropanol and acetone is 0.1mol:0.23mol:90mL. After the reaction, acetone is removed by rotary evaporation, the substrate is washed with water, the water phase is separated and vacuum dried to obtain an intermediate.

[0028] Step A2: pre-mix the intermediate, p-toluenesulfonic acid and tetrahydrofuran, introduce dry air protection, apply stirring at 40 rpm at room temperature, slowly add methacryloyl chloride to react for 1.4 hours, then raise the temperature to 45°C and continue the reaction for 2.5 hours, wherein the feed ratio of the intermediate, methacryloyl chloride, p-toluenesulfonic acid and tetrahydrofuran is 0.1 mol: 0.2 mol: 0.5 g: 60 mL. After the reaction is completed, the tetrahydrofuran is removed by rotary evaporation to obtain a modifier.

[0029] Step A3: pre-mix the modifier, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane, pass dry air for protection, then add iodopropyltrimethoxysilane and mix well, heat to 75°C, and stir at 90rpm to react for 3.5h, wherein the feed ratio of the modifier, iodopropyltrimethoxysilane, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane is 0.1mol: 0.1mol: 0.13g: 1.6g: 180mL. After the reaction is completed, filter and remove dioxane by rotary evaporation to obtain a strengthening auxiliary agent.

[0030] (2) Preparation of scratch-resistant stone-plastic composite flooring Step S1: Take the raw materials according to weight percentage, 16wt% of silica powder, selected from submicron powder with an average particle size of 0.3μm; 4.8wt% of reinforcing agent, homemade in this embodiment; 6.5wt% of active diluent, selected from industrial-grade glycidyl methacrylate; 0.18wt% of defoamer, selected from commercially available THIX-278 type silicone defoamer; 0.35wt% of leveling agent, selected from commercially available TEGO Glide100 type silicone leveling agent; the balance is difunctional B-100 type bisphenol A epoxy acrylate; first, pre-mix the acrylate resin, reinforcing agent, active diluent, defoamer and leveling agent at 180rpm for 5min, then reduce the stirring rate to 30rpm, add silica powder and mix for 30min, and vacuum degassing for 10min to obtain a protective slurry.

[0031] Step S2: Take a three-layer co-extruded stone-plastic substrate containing a stone-plastic layer, a decorative layer and an anti-wear layer, apply a 0.3 mm thick protective slurry on the surface, pre-bake and level at 60°C for 10 minutes, and send it into a UV curing oven at 120W / m 2 The protective surface layer is formed by ultraviolet radiation curing, and the scratch-resistant stone-plastic composite floor is obtained after cutting.

[0032] Example 4, preparation of scratch-resistant stone-plastic composite floor, the specific implementation process is as follows: (1) Preparation of strengthening additives Step A1: premix 1-chloropropanol and acetone, pass nitrogen protection, then add p-aminofluorobenzene, heat to 55°C, reflux and absorb the reflux tail gas with an alkaline drying tube, apply 150rpm stirring to react for 6.2h, wherein the feed ratio of p-aminofluorobenzene, 1-chloropropanol and acetone is 0.1mol:0.23mol:100mL. After the reaction, acetone is removed by rotary evaporation, the substrate is washed with water, the aqueous phase is separated and vacuum dried to obtain an intermediate.

[0033] Step A2: pre-mix the intermediate, p-toluenesulfonic acid and tetrahydrofuran, introduce dry air protection, apply 30rpm stirring at room temperature, slowly add methacryloyl chloride to react for 1.5h, then raise the temperature to 50°C and continue to react for 2.2h, wherein the feed ratio of the intermediate, methacryloyl chloride, p-toluenesulfonic acid and tetrahydrofuran is 0.1mol:0.2mol:0.5g:65mL. After the reaction is completed, remove tetrahydrofuran by rotary evaporation to obtain a modifier.

[0034] Step A3: pre-mix the modifier, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane, pass dry air for protection, then add iodopropyltrimethoxysilane and mix well, heat to 80°C, and stir at 90rpm to react for 3.3h, wherein the feed ratio of the modifier, iodopropyltrimethoxysilane, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane is 0.1mol: 0.1mol: 0.12g: 1.5g: 170mL. After the reaction is completed, filter and remove dioxane by rotary evaporation to obtain a strengthening auxiliary agent.

[0035] (2) Preparation of scratch-resistant stone-plastic composite flooring Step S1: Take the raw materials according to weight percentage, 15wt% of silica powder, selected from submicron powder with an average particle size of 0.3μm; 4.6wt% of reinforcing agent, homemade by this embodiment; 6.2wt% of active diluent, selected from industrial-grade glycidyl methacrylate; 0.18wt% of defoamer, selected from commercially available THIX-278 type silicone defoamer; 0.35wt% of leveling agent, selected from commercially available TEGO Glide100 type silicone leveling agent; the balance is difunctional B-100 type bisphenol A epoxy acrylate; first, pre-mix the acrylate resin, reinforcing agent, active diluent, defoamer and leveling agent at 180rpm for 5min, then reduce the stirring rate to 30rpm, add silica powder and mix for 30min, and vacuum degassing for 10min to obtain a protective slurry.

[0036] Step S2: Take a three-layer co-extruded stone-plastic substrate containing a stone-plastic layer, a decorative layer and an anti-wear layer, apply a 0.3 mm thick protective slurry on the surface, pre-bake and level at 60°C for 10 minutes, and send it into a UV curing oven at 120W / m 2The protective surface layer is formed by ultraviolet radiation curing, and the scratch-resistant stone-plastic composite floor is obtained after cutting.

[0037] Comparative Example 1, referring to Example 4, the reinforcing agent was replaced with the same amount of 3-trimethoxysilane propyl acrylate, and the rest of the implementation process was exactly the same.

[0038] Comparative Example 2, referring to Comparative Example 1, the amount of silica powder was increased to 22wt%, and the balance was supplemented by acrylic resin to 100wt%.

[0039] In order to verify the protective performance of the above protective surface layer on the composite floor, the protective slurry in the above implementation process is scraped into the mold sprayed with the release agent, and demolded after curing to obtain a film material. The sample is tested for pencil hardness according to GB / T 6739-2022 standard; the impact performance test is carried out according to GB / T 1732-2020 standard; the scratch resistance test includes: using CSM nano scratch tester to detect the critical load of the scratch, the loading rate is 5N / min, the load is 0-10N, and the scratch length is 5mm; using an electric cross-hatch instrument to scratch, the load is 10N, the test speed is 1000mm / min, and then using a spectrophotometer to test the color difference of the scratch; the specific test results are shown in Table 1: Table 1 Pencil hardness Impact resistance Scratch critical load Scratch color difference Example 1 4H 47 7.14 1.35 Example 2 6H 39 8.19 1.04 Example 3 5H 42 7.62 1.22 Example 4 5H 44 7.51 1.14 Comparative Example 1 5H 35 4.33 1.71 Comparative Example 2 6H 21 7.05 1.29 It can be seen from the test results in Table 1 that the protective surface layer of the composite floor of the embodiment has a relatively low hardness, a relatively high impact resistance, and good toughness. The protective surface layer is not easily damaged by external forces during use. The scratch critical load of the embodiment is high and the scratch color difference is low, indicating that it has excellent scratch resistance.

[0040] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0041] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A scratch-resistant stone-plastic composite floor, consisting of a co-extruded stone-plastic substrate and a protective surface layer, characterized in that: The components of the protective surface layer are: 14-18wt% of silicon dioxide powder, 3.5-5.2wt% of reinforcing agent, 5.5-7wt% of active diluent, 0.15-0.2wt% of defoaming agent and 0.3-0.4wt% of leveling agent, and the balance is acrylate resin; The strengthening aid is prepared by the following method: Step A1: premix 1-chloropropanol and acetone, pass nitrogen protection, add p-aminofluorobenzene, heat to 50-60°C, reflux, absorb reflux tail gas with an alkaline drying tube, stir and react for 5-7h to obtain an intermediate; Step A2: premix the intermediate, p-toluenesulfonic acid and tetrahydrofuran, pass dry air for protection, stir at room temperature and slowly add methacryloyl chloride to react for 1.2-1.6 hours, then heat to 40-50° C. and continue to react for 2-3 hours to obtain a modifier; Step A3: premix the modifier, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane, pass dry air for protection, then add iodopropyltrimethoxysilane and mix well, heat to 70-80° C. and stir to react for 3-4 hours to obtain a strengthening auxiliary agent.

2. The scratch-resistant stone-plastic composite floor according to claim 1, characterized in that: The feed ratio of p-aminofluorobenzene, 1-chloropropanol and acetone is 0.1 mol: 0.22-0.24 mol: 80-100 mL.

3. The scratch-resistant stone-plastic composite floor according to claim 2, characterized in that: The feed ratio of the intermediate, methacryloyl chloride, p-toluenesulfonic acid and tetrahydrofuran is 0.1 mol: 0.2 mol: 0.4-0.6 g: 50-70 mL.

4. The scratch-resistant stone-plastic composite floor according to claim 3, characterized in that: The feed ratio of the modifier, iodopropyltrimethoxysilane, hexadecyltrimethylammonium bromide, potassium hydroxide and dioxane is 0.1 mol: 0.1 mol: 0.1-0.15 g: 1.4-1.9 g: 150-200 mL.

5. The scratch-resistant stone-plastic composite floor according to claim 1, characterized in that: The acrylate resin is selected from difunctional acrylates.

6. The scratch-resistant stone-plastic composite floor according to claim 5, characterized in that: The acrylic resin is selected as bisphenol A epoxy acrylate.

7. The scratch-resistant stone-plastic composite floor according to claim 1, characterized in that: The reactive diluent is glycidyl methacrylate.

8. The scratch-resistant stone-plastic composite floor according to claim 1, characterized in that: Silica powder is a submicron powder.

9. The scratch-resistant stone-plastic composite floor according to claim 1, characterized in that: The defoaming agent and the leveling agent are both selected from organic silicon compounds.

10. A method for preparing the scratch-resistant stone-plastic composite floor according to any one of claims 1 to 9, characterized in that: The steps include: Step S1: premixing acrylic resin, reinforcing agent, active diluent, defoaming agent and leveling agent, adding silica powder and mixing, and vacuum degassing to obtain protective slurry; Step S2: Apply the protective slurry to the surface of the co-extruded stone-plastic substrate, pre-bake and level it, and then send it into a UV curing furnace for UV radiation curing to form a protective surface layer. After cutting, a scratch-resistant stone-plastic composite floor is obtained.